LINGUISTIC PROBLEMS IN ENGLISH ESSAY BY EFL STUDENTS - Imroatus Solikhah (Center of Language and Cultural Studies [CLCS], 2017)
This study reports linguistics problems in an essay writing by EFL undergraduate students. This study used content analysis design assigning 10 essay writing manuscripts for analysis. The 10 essays available for writing assignment were used as data sources. The study revealed that: linguistics problems appeared in terms of: syntax, sentence, grammar, tenses, and agreements. Essentially, the linguistic features in writing cover mastery on the rules of grammar. Four aspects of linguistic features are: syntax, grammar, vocabulary, and mechanics. Sentence problems, i.e. fragment, choppy, run-on, and stringy sentences, that is usually integral to syntactic and grammar problems are introduced.